ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KELAPA SAWIT DI INDONESIA - Rosi, Fahrur; Christian Sitohang, Arga; Ananta Syahbana, Javier Syarif; Widya Kumala, Dinda; Damayanti, Silvia; Masrur Mauridhoh, Mohamat (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to analyze the factors affecting palm oil exports in Indonesia, focusing on the variables of domestic palm oil production, domestic consumption, international prices, and currency exchange rates. Using secondary data from the Central Statistics Agency (BPS), Bank Indonesia (BI), and the Indonesian Palm Oil Company Association (GPKI) in the 2014-2023 period, this study uses a multiple linear regression analysis method. The results show that domestic palm oil production, international prices, and currency exchange rates have a significant influence on Indonesia's palm oil export volume. However, domestic consumption did not have a significant effect on exports. This research contributes to the development of international trade theory and provides recommendations for government policies in increasing the competitiveness of Indonesian palm oil exports.